Effect of sequence built on photonic band gap properties of one-dimensional quasi-periodic photonic crystals: Application to Thue-Morse and Double-period structures. (November 2017) - Sahel, S.; Amri, R.; Gamra, D.; Lejeune, M.; Benlahsen, M.; Zellama, K.; Bouchriha, H.
Abstract: We elaborated by Radio frequency magnetron sputtering two types of one-dimensional quasi-periodic photonic crystals, based on Si/SiO2 materials, according to the Thue-Morse sequence and the Double-period one. We have investigated their optical properties, throughout the reflection transmission spectra, experimentally as well theoretically by using the transfer matrix method. The experimental spectra of these two structures are performed at normal incident light configuration, in the near infrared wavelengths range, and, are compared for the same number of layers, for a generation number N varying from 0 to 5, corresponding to a number of layers varying from 1 to 32, respectively. We experimentally put in evidence the appearance of photonic band gaps for N higher than 2, which are then well defined for N equal to 4, for the two structures. Furthermore, the results show that these two quasi-periodic structures exhibit sharp localized modes of light within the photonic band gaps, covering the optical telecommunication wavelengths 1.33 and 1.55 μm, with different number and position depending, on the built in distribution structures. The results also show a good agreement between the experimental and calculated spectra. Highlights: Elaboration of photonic Thue-Morse and the Double-period quasi-periodic one dimensional crystal by depositing Si/SiO2 layers. Exhibition of wide photonic band gap covering telecommunication wavelengths, 1.33 μm and 1.55 μm. Existence of permit modes in the PBG depending on the nature and characteristics of the built system. Photonic Thue-Morse and the Double-period quasi-periodic structure is a good alternative for the design of mono, bi and polychromatic flexible filters.